Talent identification key : predictors of potential / Shelly Seng Shat Li - Seng, Shelly Shat Li (2012)
Talent identification has become of strategic importance for companies who wish to succeed in today’s economy. Companies are engaged in an on-going battle to attract and retain talented employees. However, this is becoming more difficult as demand for Talents surpasses supply. Therefore it is crucial for companies to be able to accurately identify the right Talents that lead the company to future success. The purpose of this study is to identify the key predictors of potential and to develop a model that will be able to accurately identify Talents. This study is conducted among Malaysian adults who are currently working and has experienced at least one performance appraisal process using a self-developed questionnaire that was administered online. The results from this study showed that only Adaptability and Analytical have a positive relationship to Talents and after controlling the effect of age.